Application of the Isotropic Material Design and Inverse Homogenization in 3D Printing - Grzegorz DZIERŻANOWSKI (Engineering Transactions, 2016)
Homogenization-based approach to structural optimization and Free Material Design (FMD) technique are discussed in case of isotropy. The problem is elaborated from the perspective provided by: (i) the theory of composites and (ii) Isotropic Material Design (IMD) – a variant of FMD. Results provided by IMD are interpreted in light of the Hashin-Shtrikman bounds on the effective isotropic properties of material-void mixtures. This in turn provides practical guidelines for 3D printing.